Mydriasis induced hyphema in a patient with rubeosis iridis - Çağatay, Halil Hüseyin; Ekinci, Metin; Çelik, Hüseyin (International Journal of Research in Medical Sciences, 2017)
Hyphema is the presence of blood in the anterior chamber of the eye. The blood may completely or partially cover the pupil and cause decrease in visual acuity. Other signs and symptoms of hyphema include visible blood in the front of the eye, pain, and sensitivity to light. The most common cause of hyphema is ocular trauma, usually a blunt or lacerating one. Other causes of hyphema include intraocular surgery, eye infections caused by herpes virus, cancer of the eye, artificial lens implants and blood clotting problems such as hemophilia, sickle cell anemia and von Willebrand disease. Hyphema may also occur spontaneously in conditions such as rubeosis iridis, juvenile xanthogranuloma, myotonic dystrophy and iris melanoma. The purpose of this case report is to point to the management of hyphema which occurs after administration of mydriatic drugs.